ANALISIS FAKTOR-FAKTOR YANG MEMENGARUHI PENDAPATAN PEDAGANG PASAR KIDUL KECAMATAN BANGLI - Marheni, Sang Ayu Made Dwi; Sudharma, I Wayan Priyana Agus (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol 14 No 2 (2025): Vol.14.No.2. FEBRUARI 2025 [123-196], 2025)
The income of traditional market traders is influenced by various factors that affect their economic well-being. This study aims to analyze the simultaneous and partial effects of education level, age, business duration, and business location on the income of traders at Pasar Kidul, Bangli Regency. The sample used in this study consists of 90 traders at Pasar Kidul. The analytical technique employed is inferential descriptive analysis using Multiple Linear Regression with the aid of SPSS 26 software. The obtained coefficient value is 0.719, with a determination value of 71.9%. This indicates that the income of Pasar Kidul traders (Y) is explained by 71.9 percent through the variables of Education Level ( ), Age ( ), Business Duration ( ), and Business Location ( ), while the remaining percentage is explained by other variables not included in the model or study. The analysis results show that the variables of education level, age, business duration, and business location simultaneously have a significant effect on the income of traders at Pasar Kidul. Partially, the variables of education level, business duration, and business location have a positive and significant effect on traders' income, while the age variable does not significantly affect the income of traders at Pasar Kidul.